Seeking Integration: Spirituality in the Context of Lifelong Learning and Professional Reflective Practice - Cheryl Hunt (Adult Education Research Conference, 2009)
This paper links two models - one of orientations to reflective practice, the other of an holistic epistemology - with empirical evidence from seminars exploring spirituality as a dimension of lifelong learning. It highlights a need for better integration within adult education and other professions of spiritual knowledge and understanding.